PENGARUH KARAKTERISTIK DEWAN TERHADAP KEBIJAKAN DIVIDEN - Yudianto, Muhammad Haris; Lastanti, Hexana Sri (Jurnal Akuntansi Trisakti, 2026)
This study aims to examine the effect of board characteristics on dividend policy in financial sector companies listed on the Indonesia Stock Exchange during the 2022–2024 period, using agency theory as the main theoretical framework. This study employs a quantitative approach with purposive sampling and obtains a sample of 39 companies with a total of 112 unbalanced panel observations. Secondary data were collected from companies’ annual reports and analyzed using panel data regression. The results show that board of commissioners size, independent commissioners, and board of directors size do not affect dividend policy. In contrast, the presence of female commissioners and female directors has a positive effect on dividend policy. These findings indicate that gender diversity on the board enhances monitoring effectiveness and improves decision-making quality, thereby reducing agency conflicts and supporting dividend distribution to shareholders. This study confirms that gender diversity on the board is an important mechanism of effective corporate governance, particularly in determining dividend policy.